The Needs Analysis on Student Module Development Based on Project-based learning Integrated with Scientific Literacy to Improve Critical Thinking Skill and Learning Independence - Faqih Abdul Bashir; Sarwanto Sarwanto; Baskoro Adi Prayitno (UIN Fatmawati Sukarno Bengkulu, 2025)
Industry 4.0 plays a vital role in the development of the world economy. The development of the world economy requires new skills, such as critical thinking skills and independent learning. Module development Project-based learning Integrated scientific literacy is needed to meet the demands of education in the 4.0 era. This research analyses the need for module development project-based learning to be integrated with scientific literacy. This type of research is survey research using quantitative descriptive research methods. The population in this study were all class VIII students at MTs N 1 Wonogiri, with a research sample of 62 students. The research was conducted in May 2024. The data collection technique used a questionnaire with a modified Likert scale with four answer choices: strongly agree, agree, disagree, and strongly disagree. The research results showed that the statements submitted to respondents obtained a percentage of 11% -40%, which fell into the categories of strongly disagree and disagree. From these results, students need a student-based science module Project-based learning integrated scientific literacy to improve students' critical thinking skills and learning independence.